2018
DOI: 10.1162/rest_a_00688
|View full text |Cite
|
Sign up to set email alerts
|

On the Demographic Adjustment of Unemployment

Abstract: The unemployment rate is one of the most important business cycle indicators, but its interpretation can be difficult because slow changes in the demographic composition of the labor force affect the level of unemployment and make comparisons across business cycles difficult. To purge the unemployment rate from demographic factors, labor force shares are routinely used to control for compositional changes. This paper shows that this approach is ill defined, because the labor force share of a demographic group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 27 publications
1
34
1
Order By: Relevance
“…In doing so, we expand a recent literature that reached conflicting conclusions on the effect of slack on the size of the multiplier: while studies based on narratively-identified shocks find little evidence for state dependence, 5 VAR-based studies find that the multiplier is largest in times of slack. 6 We find that the contractionary spending multiplier is state-dependent -being largest and around 2 in recessions-, but we find no evidence of state dependence for the expansionary multiplier -being always below 1 and not larger in recessions-. Thus, while Auerbach and Gorodnichenko (2012)'s findings have sometimes been interpreted as supporting the case for fiscal stimuli in recessions, our results caution against such a conclusion.…”
Section: Introductioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In doing so, we expand a recent literature that reached conflicting conclusions on the effect of slack on the size of the multiplier: while studies based on narratively-identified shocks find little evidence for state dependence, 5 VAR-based studies find that the multiplier is largest in times of slack. 6 We find that the contractionary spending multiplier is state-dependent -being largest and around 2 in recessions-, but we find no evidence of state dependence for the expansionary multiplier -being always below 1 and not larger in recessions-. Thus, while Auerbach and Gorodnichenko (2012)'s findings have sometimes been interpreted as supporting the case for fiscal stimuli in recessions, our results caution against such a conclusion.…”
Section: Introductioncontrasting
confidence: 67%
“…32 32 We detrend the unemployment rate to make sure that our results are not driven by slow moving trends (e.g., due to demographics) in the unemployment rate, which could make the unemployment rate a poor indicator of the amount of economic slack (see e.g. Barnichon and Mesters, 2016). Using the actual unemployment rate gives similar qualitative results for state dependence, but a posterior odds ratio calculation favors a model with detrended unemployment.…”
Section: Results From a Recursive Identification Schemementioning
confidence: 88%
“…Several studies in the literature estimate trend or natural rates of unemployment by modeling trends in the labor force flows that drive the dynamics in the UR. These analyses then calculate the trend UR as the steady-state UR implied by these estimated trend flows (Darby et al, 1985;Barro, 1988;Barnichon and Nekarda, 2012;Tasci, 2012;Meyer and Tasci, 2015;Barnichon and Mesters, 2018;Crump et al, 2019). Among these studies, Tasci (2012), Meyer and Tasci (2015), and Crump et al (2019) estimate the trends in the constituent flows in a state-space framework.…”
Section: A Tasci-fallick Estimates Of Trend Ursmentioning
confidence: 99%
“…Another paper closely related to our work is Barnichon and Mesters (2018), who estimate the trend unemployment rate. 3 They emphasize that the aggregate unemployment rate is jointly determined by the trends in group unemployment and LFP rates, and that changes in a demographic group's trend unemployment rate are likely related to changes in its trend LFP rate.…”
Section: Introductionmentioning
confidence: 97%